2009
DOI: 10.1002/jnr.22097
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of the mitochondrial permeability transition reduce ammonia‐induced cell swelling in cultured astrocytes

Abstract: Ammonia is the principal neurotoxin implicated in the pathogenesis of hepatic encephalopathy, and astrocytes are the neural cells predominantly affected in this condition. Astrocyte swelling (cytotoxic edema) represents a critical component of the brain edema in acute form of hepatic encephalopathy (acute liver failure, ALF). Although mechanisms of astrocyte swelling by ammonia are not completely understood, cultured astrocytes exposed to pathophysiological levels of ammonia develop the mitochondrial permeabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 81 publications
1
21
0
Order By: Relevance
“…From this it was concluded that mitochondrial glutamine uptake and subsequent cleavage of glutamine by glutaminase elevates mitochondrial ammonia levels, which in turn stimulates ROS production via induction of the mitochondrial permeability transition (MPT) [22,23]. Ammonia-induced astrocyte swelling was considered as a consequence of mitochondrial glutamine uptake, glutamine cleavage, MPT induction and ROS formation [24 ]. However, this view is difficult to reconcile with the fact that ammonia in cultured astrocytes induces an almost instantaneous ROS/RNS production and astrocyte swelling [12,15], whereas MPT-induction and glutamine accumulation occur thereafter [25,26].…”
Section: Ammonia and Astrocyte Swelling Induce Oxidative Stressmentioning
confidence: 99%
“…From this it was concluded that mitochondrial glutamine uptake and subsequent cleavage of glutamine by glutaminase elevates mitochondrial ammonia levels, which in turn stimulates ROS production via induction of the mitochondrial permeability transition (MPT) [22,23]. Ammonia-induced astrocyte swelling was considered as a consequence of mitochondrial glutamine uptake, glutamine cleavage, MPT induction and ROS formation [24 ]. However, this view is difficult to reconcile with the fact that ammonia in cultured astrocytes induces an almost instantaneous ROS/RNS production and astrocyte swelling [12,15], whereas MPT-induction and glutamine accumulation occur thereafter [25,26].…”
Section: Ammonia and Astrocyte Swelling Induce Oxidative Stressmentioning
confidence: 99%
“…Interests in studying ammonia toxicity in mammals arise from the fact that liver failure in human leads to the development of neurological abnormalities collectively referred to as hepatic encephalopathy, and ammonia is a key neurotoxin implicated in this condition (see Häussinger and Schliess, 2008; Lemberg and Fernandez, 2009 for reviews). More recent studies in mammals have implicated oxidative stress and mitochondrial permeability transition in the mechanism of ammonia neurotoxicity (Norenberg et al, 2005; Jayakumar et al, 2006; Pichili et al, 2007; Reddy et al, 2009; Görg et al, 2010; Häussinger and Görg, 2010). The mitochondrial permeability transition involves the opening of a pore in the inner mitochondrial membrane that leads to a collapse of ionic gradients, resulting in mitochondrial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…It is the astrocyte (the glial cells of the central nervous system) that is pivotal in providing adequate nutrition to neurons. 2 Fig. 1 shows the metabolism of ammonia and its role in HE and inflammation.…”
Section: Generalmentioning
confidence: 99%